À direita de Deus, à esquerda da Paraíba: a trajetória político-religiosa do Frei Anastácio - Luna, Emmanuel Paulino de (2023)
This work aims to analyze the political and religious trajectory of the Franciscan frei Anastácio Ribeiro, who entered the religious life in 1964, in Paraíba, becoming one of the greatest social and political leaders in the State in the following decades. In the midst of the life story of the religious, we tried to understand what dynamics allowed him to place himself in the field of the democratic left, while he also cultivated a certain prestige among Catholics. This analysis goes through the Liberation Theology (TL) debate, the class struggle and its performance as an organic religious. His biography is intertwined with the history of the struggle for land in the context of Paraíba, as Frei Anastácio made his religious mission an instrument of struggle that triggered his activity as a leftist militant, adding to his mandates as State and Federal Deputies, and other agendas linked to the poor and the workers, which assumes the justification for being the object of this thesis in Sciences of Religions, above all, because it provokes a debate of breadth that is beyond our reach, if it were treated in a generalized way. The theoretical and methodological foundation is based on Marxist and Gramscian conceptions, and other currents of thought, such as the view of man as a symbolic animal, according to Cassirer (1972) The support given to this thesis was the micro-history, and the clipping of Friar Anastácio's own life, weaving a dialogue within the transdisciplinarity of the Sciences of Religions. To obtain the necessary sources for this debate, Oral History was chosen, with semi-structured interviews provided by Frei Anastácio from a documentary, as well as people close to him who have, in a way, a connection with his trajectory. Personal and public images of the subject were also collected, as well as other written documentary sources.